Use of assistive technology in zoological collections for practical learning in zoology teaching (Research, Society and Development, 2021)
The 1988 Constitution establishes that education is a right of all and that education will be taught based on the principle of equal conditions for access and permanence in school. Thus, the main objective of this research was the elaboration of an instrument that would allow basic technical descriptions about some animal phyla deposited in zoology didactic collections for people with visual and/or hearing impairment. The result was the production of a book with information adapted through the following tools: Braille, QR Code and relief printing. All the contents of the book were made available in audio description files recorded on a CD Row. Therefore, the instrument was evaluated as the efficiency by applying a questionnaire to 10 (ten) high school students, being 6 (six) visually impaired and 4 (four) hearing impaired. It was observed that some drawings and structures more specific of the animals need to undergo few reformulations, but in general, the content was quite accepted and understood by the students. Whereas the book provided learning to the visually and hearing impaired, by promoting accessibility to the content of the zoological collection. It is also likely to provide greater equality in access to this knowledge during practical classes in which there are equivalent demands.